Anatomical Variation of Rare Thyroideaima Artery and its Role in Surgical Procedures - Sunita Bharati; N. Sujatha; Manisha Nakhate (Medical Science: Trends and Innovations Vol. 12, 2025)
Introduction: The thyroideaima artery is one of the most easily recognizable anatomical variations in the human body. its presence significantly increases the role of surgical approaches in the lower neck and superior mediastinum. Thyroideaima is a rare anomalous artery supplying the thyroid gland apart from the superior and inferior thyroid arteries. Case Report: During routine dissection of an embalmed male cadaver, approximately 65 years old, in the department of Anatomy at Shri Sathya Sai Medical College & Research Institute, Ammapettai, Chennai, this variation was observed in the thorax region. The thyroideaima artery arises from the arch of the aorta. Clinical Importance: It is of surgical importance in thyroid, parathyroid, tracheal, and mediastinal surgeries. Conclusion: The Thyroideaima artery, although a rare arterial variation, a thorough regional anatomic knowledge and meticulous dissection will not only help us in identifying such a vascular variation, but also help us in preventing an accidental injury. Emergency and surgical considerations regarding the Thyroideaima artery are critical in hemostasis and preventing hemorrhage into the mediastinal cavity.